2022
DOI: 10.21037/jtd-22-233
|View full text |Cite
|
Sign up to set email alerts
|

A study of mechanical ventilation in the ICU after cardiac surgery: a bibliometric analysis

Abstract: According to previous statistics, more than 2 million patients worldwide undergo cardiac surgery every year (1,2). Common cardiac surgical procedures include coronary artery bypass grafts, heart valve replacements, cardiac trauma repairs, and the correction of congenital heart disease. Due to the special surgical site, severe conditions, and a high incidence of postoperative complications,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Antonino et al have demonstrated a significant correlation between preoperative anemia and prolonged postoperative mechanical ventilation (MV) in patients undergoing repeat cardiac surgery, corroborating the present study’s findings [ 33 ]. Some clinical studies have suggested that preoperative anemia may be associated with multiple adverse outcomes and increased mortality after cardiac surgery [ 34 , 35 ]. Patients afflicted with anemia typically exhibit poor physical condition, frailty, or the presence of multiple comorbidities, which may contribute to the protracted requirement for postoperative MV [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antonino et al have demonstrated a significant correlation between preoperative anemia and prolonged postoperative mechanical ventilation (MV) in patients undergoing repeat cardiac surgery, corroborating the present study’s findings [ 33 ]. Some clinical studies have suggested that preoperative anemia may be associated with multiple adverse outcomes and increased mortality after cardiac surgery [ 34 , 35 ]. Patients afflicted with anemia typically exhibit poor physical condition, frailty, or the presence of multiple comorbidities, which may contribute to the protracted requirement for postoperative MV [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Independent of wavelength, energy dosage, follow-up time, and outcome criteria (occlusion/absence of reflux), a pooled analysis of EVLA in the Great Saphenous Vein a 92% overall success rate (Malskat et al, 2019). Even though similar bibliometric studies have been recently published both on cardiovascular disease and cardiovascular surgery (Huffman et al, 2013;O'Sullivan et al, 2015;Shuaib et al, 2015;Oo et al, 2020;Küçük et al, 2021;Zhang et al, 2022), no similar study was found on EVLA.…”
Section: Discussionmentioning
confidence: 99%
“…The most significant articles in their field have been determined through citation rank analysis in many medical and surgical disciplines, including cardiac surgery (10)(11)(12)(13). The most important publications in the newly-emerging field of the FET technique have not yet been determined through research.…”
Section: Introductionmentioning
confidence: 99%